2019
DOI: 10.1111/andr.12715
|View full text |Cite
|
Sign up to set email alerts
|

Reduced segregation and integration of structural brain network associated with sympathetic and dorsal penile nerve activity in anejaculation patients: a graph‐based connectome study

Abstract: Introduction Recent neuroimaging studies have indicated that some brain areas are involved in the sexual behavior process. Pre‐mature ejaculation patients exhibit altered brain activation and abnormal cortical structures. However, there has been no research evaluating the topological organization of structural brain network in anejaculation (AE). Methods We employed diffusion tensor imaging data and graph theory to examine the whole‐brain structural networks among 16 AE patients and 23 healthy controls. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…The nodes and edges are the two basic elements of the brain network. The procedures of defining the nodes and edges of the brain network have been previously described in previous neuroimaging studies [26][27][28] .…”
Section: Network Constructionmentioning
confidence: 99%
“…The nodes and edges are the two basic elements of the brain network. The procedures of defining the nodes and edges of the brain network have been previously described in previous neuroimaging studies [26][27][28] .…”
Section: Network Constructionmentioning
confidence: 99%
“…With the application of neuroimaging technologies, the close correlation between sexuality and the central nervous system (CNS) is becoming clearer (14)(15)(16). Many male sexual dysfunctions, such as ED (17)(18)(19)(20)(21)(22), premature ejaculation (23,24), and anejaculation (25) have been detected to be associated with alterations in the structure and function of the brain. For example, patients with pED demonstrated the atrophied gray matter volume (17,19), altered white matter microstructure (26), aberrant activity patterns (20), and disrupted topological properties (22) in multiple brain regions, such as prefrontal cortex, cingulate cortex, and insular cortex.…”
Section: Introductionmentioning
confidence: 99%
“…4 Using the latter technique in the present issue of Andrology, Chen and co-authors provided important new information on the specific brain neural networks involved in the regulation of erection and ejaculation. [5][6][7] In the first study, by comparing subjects with idiopathic (the term psychogenic, although still largely used, is to be considered obsolete) 8 erectile dysfunction (iED) and healthy controls (HC) they reported that cortex regions, including precuneus, precentral gyrus, middle temporal gyrus, and occipital cortex, are tightly connected with important subcortical areas including caudate nucleus, putamen, insula, and hippocampus. In addition, they found that these connections are reduced in patients with iED when compared to controls.…”
mentioning
confidence: 99%
“…9 Interestingly, in the present issue, the same Chen and co-authors reported data-derived DTI even in subjects with ejaculatory dysfunction. 6,7 In the first study, they compared 21 subjects with premature ejaculation (PE) to 27 HC. 6 Data analysis showed that subjects with PE had a significantly decreased functional connectivity in the left amygdala, right pallidum, and thalamus and decreased global efficacy in the left amygdala, right rolandic operculum, supramarginal gyrus, Heschel gyrus, inferior temporal gyrus, pallidum, and thalamus.…”
mentioning
confidence: 99%
See 1 more Smart Citation